Diabetic Distal Symmetrical Polyneuropathy: Correlation of Clinical, Laboratory, and Electrophysiologic Studies in Patients with Type 2 Diabetes Mellitus - Yi-Ching Weng; Sung-Sheng Tsai; Rong-Kuo Lyu; Chun-Che Chu; Long-Sun Ro; Ming-Feng Liao; Hong-Shiu Chang; Chiung-Mei Chen; Jawl-Shan Hwang; Hung-Chou Kuo (Journal of Diabetes Research)
This cross-sectional study is aimed at determining the prevalence of distal symmetrical polyneuropathy (DSPN) and diabetic peripheral neuropathic pain (DPNP) in participants with type 2 diabetes mellitus (T2DM); finding the risk factors for DSPN and DPNP via biochemical tests; and correlating DSPN and DPNP with the results of electrophysiologic studies, quantitative sensory tests, and neurologic examination. The 145 participants with T2DM enrolled were divided into the DSPN (abnormal nerve conduction studies (NCS) with signs of polyneuropathy), subclinical DSPN (abnormal NCS without signs of polyneuropathy), minimal DSPN (normal NCS with signs of polyneuropathy), and no DSPN groups. The biochemical risk factors of diabetic peripheral neuropathy were investigated. Neurologic examinations, laboratory tests, NCS, vibration threshold tests, and thermal threshold tests were conducted. The modified Michigan Neuropathy Screening Instrument (mMNSI) and Douleur Neuropathique 4 were used to evaluate the severity of DSPN and DPNP, respectively. In all, 30% of participants had DSPN and 11% had DPNP. DSPN correlated strongly with male gender and higher glycohaemoglobin levels; NCS abnormality correlated with higher glycohaemoglobin levels; DSPN severity correlated with NCS of each stimulating nerve. DPNP commonly occurred with clinical and electrophysiologic evidence of DSPN. Symptomatic diabetic polyneuropathy significantly correlated with longer disease duration, higher glycohaemoglobin levels, and abnormal vibration tests. The thermal threshold test combined with nerve conduction tests could detect most of the patients with DSPN, subclinical DSPN, and minimal DSPN. Poor diabetic control was independently associated with the development of DSPN. DPNP was associated with DSPN. The combination of thermal threshold tests with NCS can potentially provide the diagnosis of DSPN.